2013
DOI: 10.4236/jbise.2013.64062
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic extract association with renin inhibitors in experimental arterial hypertension

Abstract: Various epidemiological studies have shown an inverse association between the consumption of polyphenols or polyphenol-rich foods and the risk of cardiovascular diseases. The purpose of the study was to emphasize the effects of the association between the renin inhibitor and the polyphenolic extract on biochemical parameters and systolic and diastolic blood pressure. The polyphenols are extracted from isolated and purified vegetable material represented by the mature fruit of the Aronia melanocarpa. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
(11 reference statements)
1
5
0
1
Order By: Relevance
“…In our previous study, we have shown that polyphenols can act as antioxidants, due to their functional groups and aromatic structure [ 30 ]. Our finding is in agreement with Ciocoiu [ 31 ] in experimental hypertension in rats. They found reduction of systolic and diastolic pressures after treatment with Aronia melanocarpa extract.…”
Section: Discussionsupporting
confidence: 94%
“…In our previous study, we have shown that polyphenols can act as antioxidants, due to their functional groups and aromatic structure [ 30 ]. Our finding is in agreement with Ciocoiu [ 31 ] in experimental hypertension in rats. They found reduction of systolic and diastolic pressures after treatment with Aronia melanocarpa extract.…”
Section: Discussionsupporting
confidence: 94%
“…The proposed mechanism might be through inhibition of the kidney renin-angiotensin system [20]. Others also found that A. melanocarpa extract decreases blood pressure in experimental model of hypertension [21,22]. Growing evidence suggests that the flavonoid-rich foods intake is related with decline in SBP and DBP, so we assume that the blood pressure-lowering effect of SAE is attributed to polyphenols [22,23].…”
Section: Discussionmentioning
confidence: 88%
“…The high antioxidant activity of berries makes their effective utilization in the treatment of chronic diseases related to oxidative stress possible, especially diabetes, cardiovascular diseases and cancer. Except for the mentioned properties, numerous other positive medicinal and therapeutic benefits, namely immunomodulatory, antibacterial, hepatoprotective, gastroprotective and anti-inflammatory, have been demonstrated for black chokeberry extracts both in vitro, in cells or cell lines, and in in vivo studies in humans or animals [ 22 , 23 , 24 , 99 , 100 , 101 , 102 , 103 ].…”
Section: Chokeberry Fruit and Its Health-promoting Activitymentioning
confidence: 99%
“…That is a reason why Aronia species are at the top of fruits and berry species and why they display the wide range of activities in relation to chronic diseases, especially heart and cardiovascular [ 18 , 19 , 20 ] ones, involving antiatherosclerotic, hypotensive and antiplatelet properties [ 17 ]. Due to the presence of these bioactive compounds, the berries of Aronia exhibit also other biological, health-promoting effects both in vitro and in vivo, such as gastroprotective (stomach ulcers), hepatoprotective, antiproliferative activities (e.g., colon cancer), prevention and treatment of diabetes [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%